Ethnobotanical study of local wisdom on the Jembul Jepara tradition as a reference book - Syafira Ulfi Arifa; Serafica Btari Christiyani Kusumaningrum; Ericka Darmawan (University of Muhammadiyah Malang, 2024)
The diversity of cultures in Indonesia, one of which is the Jembul Tradition, can be implemented through ethnobotanical studies that can support community knowledge. The purpose of this study is to find out the ethnobotanical profile in the Jembul Tradition and analyze the feasibility of reference books based on experts. The research method uses mixed research, namely descriptive research including ethnographic research and R&D (Research and Development) development research with the 4D development method. Data collection was carried out by interviews, observations, and documentation. The feasibility of reference books is carried out by validation from material experts and the media and then tested for public readability. The results of the study were obtained from 35 types of plants which were grouped into 22 orders. The developed reference books have been validated by material and media experts with an average of 84% with a very feasible category. The percentage of readability by the public was obtained on average 93.8% with a high category. It can be concluded that the book developed is worthy of being used as a source of knowledge for the general public.